The Balance of Academic, Emotional, and Spiritual Intelligence in the Qur’an (An Analysis of Tafsir Al-Misbah on QS. Al-‘Alaq: 1–5 and QS. Al-Hajj: 46) - Putri Ega Aulia; Amroeni Drajat (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to explore the concept of intelligence from the perspective of the Qur’an by examining its academic, emotional, and spiritual dimensions, as well as their relevance to contemporary life. The research focuses on Surah Al-‘Alaq verses 1–5 as the foundation of intellectual (academic) intelligence, and Surah Al-Hajj verse 46 as the basis for emotional and spiritual intelligence. Employing a qualitative approach, this study is conducted through library research using a thematic (maudhu‘i) interpretation method. The primary sources include the Qur’an and Tafsir Al-Misbah by M. Quraish Shihab, supported by various relevant scholarly works. Data are collected through documentation techniques and analyzed using an inductive method. The findings indicate that the Qur’an presents intelligence as an integrated concept encompassing the intellect (‘aql), the heart (qalb), and the soul (ruh). Achieving balance (tawazun) among these elements is essential for developing a complete individual one who possesses strong character, adaptability, and the ability to navigate modern life in a balanced and harmonious way.